Retinal Hyperreflecting Foci Associate With Cortical Pathology in Multiple Sclerosis. Issue 4 (23rd July 2022) - Pengo, Marta; Miante, Silvia; Franciotta, Silvia; Ponzano, Marta; Torresin, Tommaso; Bovis, Francesca; Rinaldi, Francesca; Perini, Paola; Saiani, Martina; Margoni, Monica; Bertoldo, Alessandra; Sormani, Maria Pia; et al.
Abstract : Background and Objectives: Microglia, the resident immune cell of the brain and retina, is widespread activated in the white and gray matter (GM) in multiple sclerosis (MS). The objective of this study is to evaluate the presence and number of hyperreflecting foci (HRF), considered clusters of activated and proliferating retinal microglia, and their association with clinical and radiologic disease parameters in relapsing-remitting MS (RRMS). Methods: At baseline, 80 patients with RRMS underwent optical coherence tomography (OCT) and 3T-MRI (including 3-dimensional T1, fluid-attenuated inversion recovery, and double inversion recovery sequences), closed to their disease onset (6.3 ± 5.1 months). These patients were then clinically and radiologically followed up for a mean of 43 months, evaluating the no evidence of disease activity (NEDA) condition, further divided into clinical (cNEDA) and radiologic (rNEDA). Patients with a clinical history or MRI/OCT findings suggestive of optic neuritis (ON) were excluded from the study. Results: Compared with healthy controls, the HRF number was significantly higher in the inner nuclear layer (INL) of patients with RRMS (19.55 ± 5.65 vs 13.84 ± 2.57, p < 0.001) and associated with INL volume (β: 1.21, p < 0.001). GM lesion volume significantly correlated with the INL HRF count ( p = 0.008). Survival analysis revealed a significant association between INL HRF and both cNEDA ( p = 0.017) and rNEDA ( p = 0.002). Discussion: We found a strong association between retinal microglial proliferation and cortical pathology in RRMS, a finding suggesting a possible underlying common immunopathologic mechanism. Furthermore, microglial activation at baseline was observed to predict subsequent inflammatory events, indicating that HRF might be a candidate prognostic biomarker worthy of further investigation. Classification of Evidence: This study provides Class II evidence that in patients with early RRMS but without ON, the number of HRF on OCT of the retinal inner nuclear layer is associated with cNEDA and rNEDA.